The thickness of labial bone affects the esthetics of immediate implant placement and provisionalization in the esthetic zone: A prospective cohort study. (29th April 2019) - Yang, Xingmei; Zhou, Tengfei; Zhou, Nan; Man, Yi
Abstract: Background: A 1‐2 mm thick labial plate is generally advocated in immediate implant placement and provisionalization (IIPP). However, most of the human labial plates fail to meet this requirement. Purpose: This study aimed to investigate the effect of labial plate thickness on hard tissue, soft tissue, and esthetic outcomes in IIPP. Materials and Methods: In this prospective cohort study, 40 patients received IIPP of 50 single‐crown implants in the anterior maxilla. Patients were categorized into three groups according to their presurgical thickness of labial bone: 0‐0.5, 0.5‐1, and ≥ 1 mm. CBCT, mucosa recession and the papilla index were used to analyze labial hard and soft tissue alterations with a 1‐year follow‐up. Results: At 1 year, OCI bone losses were 1.17 ± 0.73, 0.37 ± 0.39, 0.46 ± 0.35 mm; ICH bone losses were 2.23 ± 1.83, 0.74 ± 0.71, 0.72 ± 1.27 mm; TM recessions were 1.00 ± 0.51, −0.06 ± 0.37, −0.30 ± 0.88 mm; TL recessions were 0.61 ± 1.02, −0.18 ± 0.40, −0.26 ± 1.15 mm; TD recessions were 0.61 ± 1.02, −0.18 ± 0.40, −0.26 ± 1.15 mm; PIS scores were 1.63 ± 0.64, 2.20 ± 0.71, 2.71 ± 0.57 in group 0‐0.5, 0.5‐1 and ≥ 1 mm, respectively. No statistical significance was found between group 0.5‐1 and ≥ 1 mm in bone resorption, gingival recession, and papilla index. The bone resorption and gingival recession were significantly the highest in group 0‐0.5 mm at 6 months and 1 year. Conclusions: Group 0.5‐1 mm had similar tissue dimensional alteration as group ≥1 mm, while group <0.5 mm suffered more massive bone resorption and gingival recession. Concerning the thickness of the labial plate, this study may suggest an expansion in the indication of IIPP.